PENGARUH KONFLIK DAN STRES KERJA TERHADAP PRODUKTIVITAS TENAGA PENDIDIK DI MA BIROYATUL HUDA CILONGOK - Handayani, Anggi Nuril (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the impact of workplace conflict and job stress on the productivity of educational staff at MA Biroyatul Huda Cilongok. Using a qualitative approach through semi-structured interviews and observations, the research explores the relationship between workplace conflict, job stress, and the productivity of educational staff. The findings indicate that workplace conflict, often arising from misunderstandings among colleagues or with management, disrupts communication and collaboration, thereby reducing work efficiency. Job stress, caused by administrative burdens and role pressures, further exacerbates the situation by diminishing motivation and concentration among educational staff. The combination of workplace conflict and job stress significantly affects productivity. However, effective management strategies, such as mediation and stress management training, can improve overall performance. This study emphasizes the importance of fostering a harmonious work environment to enhance the productivity of educational staff.